2021
DOI: 10.3389/fcell.2021.720649
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of a Malignant Cell Subset Marker-Based Polygenic Risk Score in Stomach Adenocarcinoma Through Integrated Analysis of Bulk and Single-Cell RNA Sequencing Data

Abstract: Objectives: The aim of the present study was to construct a polygenic risk score (PRS) for poor survival among patients with stomach adenocarcinoma (STAD) based on expression of malignant cell markers.Methods: Integrated analyses of bulk and single-cell RNA sequencing (scRNA-seq) of STAD and normal stomach tissues were conducted to identify malignant and non-malignant markers. Analyses of the scRNA-seq profile from early STAD were used to explore intratumoral heterogeneity (ITH) of the malignant cell subpopula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Zou et al . [ 55 ] also proposed complete responses to drug therapies are rare in tumours, and only some but not all subpopulations in a given tumour response to therapy. Single‐cell analysis revealed that most genes in the 28‐GPS were not only expressed in cancer cells but also in stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zou et al . [ 55 ] also proposed complete responses to drug therapies are rare in tumours, and only some but not all subpopulations in a given tumour response to therapy. Single‐cell analysis revealed that most genes in the 28‐GPS were not only expressed in cancer cells but also in stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…As well, the TIMER tool is a comprehensive resource designed to analyze immune cell infiltrates across diverse cancer subtypes (139). The TCGA has a publicly available human stomach adenocarcinoma (STAD) dataset containing clinical annotations along with molecular profiles that were utilized as a reference or primary dataset in several studies (25,28,36,37,41,45,133). FirebrowseR, also generated by the Broad Institute, is a database which provides access to the PanCanAtlas, containing conserved cancer gene expression data (134).…”
Section: Tools For Analyzing Gastric Cancer Scrnaseq Datamentioning
confidence: 99%
“…Most groups obtained primary gastric cancer tissues from patients to generate scRNAseq data (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Some utilized previously published primary tumor datasets for further analysis (36)(37)(38)(39)(40)(41)(42)(43). Others transcriptionally profiled "liquid biopsies" of metastatic ascites fluid taken from gastric cancer patients (44,45).…”
Section: Introductionmentioning
confidence: 99%
“…The advantageous difference of increased granularity is tantamount—scRNA-seq faithfully represents cellular heterogeneity by distinguishing gene expression profiles between different cell types, and even between the same cell type in different cellular states ( Lähnemann et al, 2020 ). The advances in medicine made possible by scRNA-seq are invaluable, e.g., scRNA-seq enabled Zou et al (2021) to develop a prognostic signature in gastric adenocarcinoma, Deng et al (2020) identified characteristics predicting CAR T cell therapy efficacy. Toxicology can follow suit to develop targeted therapies for the myriad of multi-cell-type health problems associated with environmental exposure to chemicals, including cancer ( Snyder, 2012 ), asthma ( Sachdeva et al, 2019 ), and infertility ( Canipari et al, 2020 ; Selvaraju et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%